Problematika Perlindungan Hukum Terhadap Anak Korban Incest: Tantangan Dan Harapan - Wevy Efticha Sary; Fakhriyah Annisa Afroo (Jurnal Ilmiah Kutei, 2025)
The phenomenon of incest as a form of sexual violence against children within the family environment is a serious issue that often remains hidden, as it occurs in private spaces and is accompanied by emotional pressure and power dominance. Children as victims are placed in a highly vulnerable position—physically, psychologically, and socially. The crime of incest remains difficult to address effectively because the current Indonesian Penal Code (KUHP) does not explicitly regulate incest as a distinct criminal offense. However, Indonesia has enacted the Child Protection Law, the Law on the Elimination of Domestic Violence (PKDRT), and the Law on Sexual Violence Crimes (UU TPKS), which can be applied to cases of incest. This research aims to explore two main problems: how legal protection for child victims of incest is regulated under Indonesian legislation, and what challenges exist in the law enforcement process concerning incest cases involving children. This study employs a normative legal research method with a descriptive-analytical and legal-political approach. Data were collected through a literature review of statutory regulations, legal doctrines, scholarly journals, and institutional reports. The findings reveal that although legal norms provide a framework for protection, the implementation is hampered by evidentiary limitations, familial pressure, insufficient sensitivity among law enforcement officers to the psychosocial conditions of child victims, and the pervasive influence of patriarchal values. Therefore, comprehensive legal reform is urgently needed one that centers on the rights and recovery of victims through trauma-informed and restorative justice approaches.